Proses Pengembangan Kurikulum Pendidikan Agama Islam - Yuni Listiyani; Wama Fima; Insanul Mizan; Mustafiyanti Mustafiyanti (IHSANIKA : Jurnal Pendidikan Agama Islam, 2023)
This study aims to explain the process of developing the Islamic Religious Education curriculum using library research methods, namely the library approach by studying books, journals, and other relevant sources. The result of this writing is the process of developing a curriculum with Islamic religious education, it is in the process to what extent the curriculum with Islamic religious education, while in the process it takes a long time to perfect the curriculum with Islamic religious education, as for curriculum development that is designed with ideas and programs, in the process. This idea is in the form of a document in the form of a syllabus, so with the development process it will be developed and socialized by the community and educational institutions. The process of this educational curriculum can be developed with the design, implementation and completion of the Islamic religious education curriculum.